Amazônia, UNASUL e desenvolvimento sustentável: o papel do Brasil (2003-2010) - Campos, Rogério Pereira de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The significant growth of the countries in South America, concomitant with the process of globalization highlighted the region to confront new global proposals in the social, economic and environmental issues. The challenges for a better integration of these nations in the world today demands improvements in all spheres, like economic, social and environmental knowledge as well as closer ties between them. This study aims to analyze the challenges present in the process of forming the Union of South American Nations (UNASUL) originated in 2004 and its possibilities for improving social, political, economic and environmental sustainability in South America and the direct influence of Brazil in this process, either positive or negative. In the middle of this process is important to consider the issue of Amazon, with its uncertainties and resources. This isn‟t only a natural border, but a sub-region to be inserted in the process to build a consistent region like is South America. The need for such an immense sub-region conflicts with the obligation to preserve and monitor the ecosystem Amazon that is very rich and diverse. But this preservation is not feasible following trends imposed by neoliberalism in the exploitation of resources without limits imposed by market rules. Thus, for the alleged integration occurs there is the challenge of sustainable use of the Amazon rainforest while creating favorable conditions for the transit of people and goods, combined with best social and economics conditions

O crescimento significativo dos países da América do Sul no período em estudo, concomitante com o aprofundamento do processo de globalização, colocou em evidência a região frente às novas propostas globais nas questões sociais, econômicas e ambientais. Os desafios para a melhor inserção das nações da América do Sul no mundo atual demandam melhorias em todas as esferas, tanto sócio-econômicas e ambientais como de conhecimento e também de uma maior aproximação entre elas. Este estudo visa analisar os desafios presentes no processo de conformação da União das Nações Sul-americanas (UNASUL) originada em 2004 e suas possibilidades para a melhoria social, política, econômica e ambiental da América do Sul e a influência direta do Brasil neste processo, seja positivo ou negativo. No meio desse processo importa considerar a problemática da Amazônia, com suas demandas e recursos. Ela não é uma fronteira natural, mas sim uma sub-região a ser inserida no processo da construção homogênea da região que é a América do Sul. A necessidade de utilizar tão imensa sub-região pode conflitar com a obrigação de preservar e vigiar o ecossistema amazônico que é muito rico e diverso. Sua necessária preservação seria inviável seguindo tendências impostas pelo neoliberalismo na exploração dos recursos sem limites impostos pelas regras do mercado. Dessa forma, para a pretensa integração ocorrer tem-se o desafio de utilizar de forma sustentável a floresta amazônica criando, simultaneamente, condições favoráveis ao trânsito de pessoas e mercadorias, combinado com melhores condições socioeconômicas
Keywords: União de Nações Sul-Americanas; Sustentabilidade; Meio ambiente; Desenvolvimento sustentável; Sustainable development; Amazônia